REAKSI PASAR TERHADAP PENGUMUMAN SAHAM BONUS DI BURSA EFEK INDONESIA - Ratna Dewi, Ni Putu Desy; Sukartha, I Made (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
The announcement of bonus shares is policies issued by the company as a form of information published about the company's future prospects. The purpose of this study is to determine the market reaction to the announcement of bonus shares on the Indonesia Stock Exchange. Market reaction may be indicated by the presence of abnormal return in the event period. Event period is set for 7 days with a sample of firms that do bonus shares amounting to 14 companies and 17 events of bonus shares. Testing hypothesis 1 using a one sample t-test and the test results show that there is a negative and significant AAR that occurred on the date of announcement of bonus shares. Testing hypothesis 2 using paired sample t-test and the test results showed that there was no significant difference in abnormal returns before and after the announcement of bonus shares.
Keywords: Abnormal return, Bonus Shares, Event Study, Market Reaction